BENCHMARK OF COUNTRIES’ PERFORMANCE IN LOGISTICS: AN APPROACH BASED ON WORLD BANK OPEN DATA - Minnow, Maclar Daniel; Eric, Quansah; Bányai, Tamás (Advanced Logistic Systems - Theory and Practice, 2022)
Logistics which can be considered as the science of planning, implementing and controlling the physical flow of materials and goods from point of origin to point of use to meet customer`s need at a profit has become very important in recent times that it now plays a vital role in companies’ performance as well as the economies of nations. One of the attempts to measure logistics performance at national level is the Logistics Performance Index (LPI) published by the World Bank Group. In fact this study dubbed ”Benchmark of countries’ performance in Logistics – an approach based on World Bank Open Data” argues that there is a close relationship between global competitiveness level of a country and its logistics performance level. It discusses some types of Logistics and also aims to analyze the logistics competitiveness of some countries from a national competitiveness perspective using World Bank Open Data. This work sought to compare Logistics Performance Index (LPI) of Ghana and its region as well as Hungary and its region. Finally, the work made use of international score card where six key dimensions (thus Customs, Infrastructure, International shipments, logistics competitiveness, Tracking & tracing and Timeliness) are applied to benchmark countries' performance and also display their derived overall LPI index to discuss Logistic Performance of Hungary together with that of Ghana.